APLIKASI AL KALAM DALAM MENINGKATKAN MOTIVASI MEMBACA ALQURAN - Nur, Muhammad (LPPM IAIN Parepare, 2018)
The purpose of this study was to determine the differences in the level of motivation to read the al-Qur?an by using the Al Kalam application on Alquran Writing and Reading subjects in SMP 5 Duampanua. The research used experimental research with treatment by level design technique, to analyze and tes the hypothesis of the author using the percentage and Uji t by SPSS 21 version with analysis of two-lane variants. According to the results of the study, there is a level of motivation to read the al-Qur?an by using the Al Kalam application based on the frequency of the percentage that the experimental class is in the high category. The implication shows that there are differences in the level of motivation to read the Koran using the Al Kalam application in the experimental class, compared to the level of motivation of students who do not use the Al Kalam application.